Structure and Optical Properties of ZnCdO Thin Films Prepared by Spray Pyrolysis - Khlaief, Jabbar H (Al-Nahrain Journal of Science, 2018)
ZnCdO films were compounded by spray pyrolysis on glass substrates at temperature of 250Co, using solution of zinc acetate and cadmium acetate salts with various additions concentrations of Zn (25, 50, 75)%. Structure and optical properties have been analyzed using XRD and UV-Vis spectroscopy. XRD analysis premiered that thin films were of polycrystalline nature with face centered cubic structure. The crystallinity increases when the Zn additions increases. Film additions with 75% Zn has minimum value of dislocation density and strain which confirm the improved crystallinity of the film. The optical results featured the transparency of the ZnCdO films is greater than 80% in the visible region, and we found when the concentration of Zn additions increase the optical band gap increasing from (2.49 to 2.9eV).